1995
DOI: 10.1093/oxfordjournals.aje.a117575
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to Polychlorinated Dioxins and Furans (PCDD/F) and Mortality in a Cohort of Workers from a Herbicide-producing Plant in Hamburg, Federal Republic of Germany

Abstract: The relation between mortality (all cause; cancer; cardiovascular diseases (International Classification of Diseases, Ninth Revision (ICD-9), codes 390-459); ischemic heart diseases (ICD-9 codes 410-414)) and exposure to polychlorinated dibenzo-p-dioxins and -furans (PCDD/F) was investigated in a retrospective cohort study. The cohort consisted of 1,189 male workers in a chemical plant in Hamburg, Federal Republic of Germany, who had produced phenoxy herbicides, chlorophenols, and other herbicides and insectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 0 publications
10
107
0
1
Order By: Relevance
“…A similar elevation in mortality from cardiovascular disease has been reported in occupational studies of dioxin-exposed workers (Flesch-Janys et al, 1995;Vena et al, 1998) and Seveso residents exposed to dioxin releases Pesatori et al, 1998). Sergeev and Carpenter (2005), examining rates of hospitalization for cardiovascular disease and acute myocardial infarction in residents living in zip codes containing or abutting hazardous waste sites contaminated with persistent organic pollutants, found statistically significant elevations of cardiovascular disease compared to populations not living near such waste sites.…”
Section: Discussionsupporting
confidence: 72%
“…A similar elevation in mortality from cardiovascular disease has been reported in occupational studies of dioxin-exposed workers (Flesch-Janys et al, 1995;Vena et al, 1998) and Seveso residents exposed to dioxin releases Pesatori et al, 1998). Sergeev and Carpenter (2005), examining rates of hospitalization for cardiovascular disease and acute myocardial infarction in residents living in zip codes containing or abutting hazardous waste sites contaminated with persistent organic pollutants, found statistically significant elevations of cardiovascular disease compared to populations not living near such waste sites.…”
Section: Discussionsupporting
confidence: 72%
“…TCDD serum concentrations reported for TCDD-exposed populations, ordered by year of serum sampling, are listed in Table 6. This indicates that the New Zealand serum concentrations back-calculated to 1987 are lower than those reported for the USA (Fingerhut et al 1991) and Russian (Ryan and Schecter 2000) production workers, while comparable to levels reported for German (Flesch-Janys et al 1995), Dutch (Heederik et al 1998) and US Michigan (Collins et al 2007) production workers. The New Zealand mean TCDD serum concentrations determined in 2007/2008 are also comparable with those reported for 777 US Air Force veterans of Operation Ranch Hand tested in 2002 (Pavuk et al 2014).…”
Section: Discussionsupporting
confidence: 48%
“…Many epidemiologic studies have supported the notion that exposures to persistent organic pollutants (POPs) contribute to an increased risk of cardiovascular diseases. For example, persons having high concentrations of POPs such as polychlorinated biphenyls (PCBs) and 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) due to occupational or accidental exposures showed weakly or modestly elevated mortality due to cardiovascular events [12][13][14][15][16]. More recently, other studies have shown that residents living near areas contaminated with POPs had greater incidences of heart diseases and hypertension than those living in relatively clean areas [9,17].…”
Section: Discussionmentioning
confidence: 99%